Relationships between understanding writing from sources, originality and plagiarism in academic writing of ESL graduate students in science and engineering programs - Saadabadimotlagh, Hossein (2017)
The actual practice of writing from sources is rarely as straightforward for ESL students as it is usually described and taught. Many factors govern how ESL graduate students appropriate source texts in their writings for academic purposes. Low language proficiency, limited vocabulary, and unfamiliarity with the discourse of the discipline lead ESL graduate students to borrow language from writings of experts in their field to gain authorial identity and discipline membership. However, inadequate knowledge and skill in source citation, coupled with low level of understanding plagiarism makes ESL students vulnerable to the accusation of plagiarism despite their sincere attempt not to do so. Reviewing the research on plagiarism studies turned out that most cases of accusation of plagiarism in academic writings of ESL students stem in a few reasons including borrowing text from other sources and inadequate citation of the texts they borrow. The literature also indicated that the problem is more challenging among graduate students in science and engineering programs. Therefore, in the present thesis two goals were formulated, and two procedures were followed. First, a qualitative study was designed to develop a questionnaire that can quantify how Iranian ESL graduate students in science and engineering programs in Malaysian universities think of, and decide on textual borrowing and citation practices. Then, through a quantitative analysis of the results, an attempt was made to develop a quantitative model for predicting originality of language in the academic writings of the participants of the study. The model was then contextualized by comparing with the findings of the qualitative phase and the literature. Results indicated three groups of respondents with regard to their understanding and view of textual borrowing and source citation. The first group was labeled Basic Academic Practitioners (BAP), who had no idea of or a wrong view of source use. Another group included Informant Academic Practitioners (IAP), who were familiar with the locally accepted norms of source use, and finally, the third group was labeled Advanced Academic Practitioners (AAP) whose members were familiar with the international conventions of writing from sources. The examination of the relationship between students’ understanding of source citation decision and textual borrowing, with the originality of language in their actual academic writing performance through multiple regression analysis indicated no significant relationship between the variables. Results also indicated that neither students’ view of textual borrowing nor their view of source citation were significant predictors of originality of language among participants of this study. The results obtained from this research revealed a distinction between what is actually practiced as academic writing in the Iranian academic contexts and the real nature of academic writing. This study also indicated a need for especial attention to teaching academic writing in terms of materials and methods in the Iranian academia, especially in science and engineering fields.